Jezebel as Voiced by Others in 1 and 2 Kings - Joachimsen, Kristin (Die Welt des Orients, 2020)
Against a tendency to depict Jezebel as a rather one-dimensional, homogenous, and contrastive actor, this study offers an analysis of the complexity of her portrayal in 1-2 Kings. The analysis takes the imperial setting into account, with a particular focus on the relationship between gender, religion, and politics. The study relates the portrayals of Jezebel and the other actors she is encountering to the different contexts in which they are embedded, that is, intersecting identities within a narrative that is located in a remembered past, an internal Judean discourse as well as a broader imperial context. The portrayal of Jezebel suits the needs of those who produced and interpreted her story, as it tells something about Israel under the empire, not least about her husband, King Ahab, but also about Yahweh.